KEWENANGAN MAHKAMAH KONSTITUSI PADA SENGKETA HASIL PEMILIHAN KEPALA DAERAH - Tantry Octaviani, Putu; Parikesit Widiatedja, I Gusti Ngurah (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015)
This writing shall be entitled as “The Authority of The Constitutional Court on The Result of Local Election’s Dispute". With normative, descriptive, evaluation and legal argumentation research, combined with statutory approach in its composition, this writing shall dicuss the authority of Constitutional Court before and after the existence of Constitutional Court Decision No.97/PUU-XI/2013. Before the issuance, the Constitutional Court has the right to resolve the dispute on the result of regional election. But it’s unconstitutional since Local Government and General Election was organized in a different chapter. After that desicion, the Constitutional Court has no right to resolve the dispute. Alternative that can be taken is giving authority to the High Administrative Court to resolve the dispute by publishing laws immediately.
Keywords: Authorities, Constitutional Court, Dispute, Local Election